(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
In the late Middle Ages, social distinction was expressed through the possession and consumption of rare and precious movable goods. In addition to exotic foods and high-quality wines, clothing, jewelry, and artistic objects played a crucial role in defining social status. However, an often overlooked aspect is the role of artificial lighting. Candles, lamps, and candelabras not only had practical functions but also served to enhance the social prestige of their owners. These objects, often made of precious metals such as gold and silver, illuminated domestic and religious environments, amplifying their splendor. Their presence and use during ceremonies and banquets were eloquent symbols of wealth and power. Analyzing these artifacts provides a deeper understanding of medieval material culture and the symbols of social distinction.